2012
DOI: 10.1002/pbc.24261
|View full text |Cite
|
Sign up to set email alerts
|

Sleep, fatigue, depression, and quality of life in survivors of childhood acute lymphoblastic leukemia

Abstract: Differences in parental and self-reports, including worse parental ratings, might be explained by worried parents and/or the adaptive style of the children. Impaired sleep and fatigue correlated with more depressive symptoms and a worse QoL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
99
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(117 citation statements)
references
References 43 publications
11
99
0
7
Order By: Relevance
“…Parent-proxy report of symptoms in adolescents is known to differ significantly from adolescent self-report. In a study of acute lymphoblastic leukemia (ALL) survivors, Gordijn et al (2013) found that parent-reported sleep disturbance was significantly related to increased depressive symptoms and poor quality of life per parents' report; however, ALL survivors reported better sleep quality and fewer depressive symptoms than their healthy peers. These conflicting subjective reports indicated the need for further study in this population using validated surveys.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Parent-proxy report of symptoms in adolescents is known to differ significantly from adolescent self-report. In a study of acute lymphoblastic leukemia (ALL) survivors, Gordijn et al (2013) found that parent-reported sleep disturbance was significantly related to increased depressive symptoms and poor quality of life per parents' report; however, ALL survivors reported better sleep quality and fewer depressive symptoms than their healthy peers. These conflicting subjective reports indicated the need for further study in this population using validated surveys.…”
Section: Discussionmentioning
confidence: 96%
“…Although these studies provide valuable information on the nature of sleep in this patient population, findings cannot be generalized to the broader population of survivors of childhood cancer because the etiology of sleep disturbance in survivors of CNS tumors may differ from that of other cancer survivors. To date, only one other study explored associations between reported sleep problems and negative sequelae associated with impaired sleep in an adolescent survivor population (Gordijn et al, 2013).…”
mentioning
confidence: 99%
“…Studies including AYA have done so as part of a larger age range (either childhood or adulthood) without specific subgroup analyses. Such research has described higher instances of disrupted sleep among survivors ages 5–17 relative to norms [11], sleep disturbances in 49 % of acute lymphoblastic leukemia survivors ages 18–41 [3], and sleep efficiency (percentage of time in bed asleep) below 85 % suggestive of insomnia in almost one third of 20–48-year-old survivors [12]. The Childhood Cancer Survivor Study (ages 18–50+) found slightly higher rates of sleep disturbances (16 %) in survivors relative to siblings (12 %) and that survivors were 1.9 times more likely to be fatigued than sibling controls [13].…”
mentioning
confidence: 99%
“…During treatment, the child is isolated from his/her school, friends, and family members. All these factors impair the quality of life of the children and their families and induce psychological problems (7)(8)(9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%